Risk and subtypes of secondary primary malignancies in diffuse large B‐cell lymphoma survivors change over time based on stage at diagnosis. Issue 1 (11th September 2019) - Major, Ajay; Smith, Derek E.; Ghosh, Debashis; Rabinovitch, Rachel; Kamdar, Manali
Abstract : Background: Previous studies have shown an increased risk of secondary primary malignancies (SPMs) after diffuse large B‐cell lymphoma (DLBCL) treatment. Whether stage of DLBCL at diagnosis affects the subtypes of SPMs that occur has not been previously described. Methods: The Surveillance, Epidemiology, and End Results database was queried for patients aged >18 years diagnosed with primary DLBCL from 1973 to 2010 and categorized by early stage (ES) (stage I‐II) or advanced stage (AS) (stage III‐IV) disease. Differences in overall and location‐specific SPM incidence by stage and time since diagnosis were assessed in 5‐year intervals using a Fine‐Gray hazards model. Overall survival was compared using the log‐rank test. A Cox proportional hazards model was used to assess differences in survival. Results: In total, 26, 038 patients with DLBCL were identified, including 14, 724 with ES and 11, 314 with AS disease. The median follow‐up was 13.3 years. Overall, 13.0% of patients developed SPM, with a higher but nonsignificantly increased risk of SPM development in those who had ES disease compared with those who had AS disease (14% vs 11.6%; P = .14). During the first 5 years after diagnosis, patients who had ES disease had a higher risk of SPM than those who had AS disease, specifically colorectal, pancreas, breast, and prostate SPMs. During the period from 10 to 15 years after diagnosis, patients who had AS disease had a higher risk of SPM than those who had ES disease, specifically hematologic SPMs. Development of SPM was found to significantly increase the risk of death regardless of stage at diagnosis. Conclusions: In this large, population‐based study, distinctly different subtypes and temporal patterns of SPM development were identified based on stage of DLBCL at diagnosis. The current study merits consideration of tailored site‐specific and time‐specific surveillance for patients with DLBCL according to stage and time interval since diagnosis. Abstract : In adult survivors of diffuse large B‐cell lymphoma, there is a nonsignificantly increased risk of secondary primary malignancies (SPMs) for those who survive early stage versus advanced‐stage disease, and the development of SPM is associated with a significantly increased risk of death regardless of stage at diagnosis. When studied in 5‐year intervals after diagnosis, there is a significantly increased risk of colorectal, pancreas, breast, and prostate SPMs for those with early stage disease in the first 5 years after diagnosis and a significantly increased risk of hematologic SPM in those with advanced‐stage disease in the period from 10 to 15 years after diagnosis.